2020
DOI: 10.1073/pnas.2000258117
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to helpless behavior is regulated by the circadian clock component CRYPTOCHROME in the mouse nucleus accumbens

Abstract: The nucleus accumbens (NAc), a central component of the midbrain dopamine reward circuit, exhibits disturbed circadian rhythms in the postmortem brains of depressed patients. We hypothesized that normal mood regulation requires proper circadian timing in the NAc, and that mood disorders are associated with dysfunctions of the NAc cellular circadian clock. In mice exhibiting stress-induced depression-like behavior (helplessness), we found altered circadian clock function and high nighttime expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 105 publications
(131 reference statements)
4
35
0
Order By: Relevance
“…Previous studies from our lab have found in mice that core clock genes Npas2 , Clock and Period all show diurnal variation in the NAc (Falcon et al, 2013), as well as rhythmicity measured by Per2 :luciferase luminescence assays (Logan et al, 2015). This is further supported by studies from the Welsh group demonstrating NAc Per2 :luciferase rhythms (Landgraf, Long, & Welsh, 2016; Porcu et al, 2020), as well as diurnal variation in CRYPTOCHROME protein levels in the NAc (Porcu et al, 2020). Interestingly, this is also seen in time of death analyses of gene expression in human post‐mortem tissue, where the canonical clock genes (e.g., Bmal1 , Npas2 , Period , Cryptochrome , Rev‐erbα ) are all highly rhythmic in the NAc of healthy donors (Ketchesin et al, 2021; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies from our lab have found in mice that core clock genes Npas2 , Clock and Period all show diurnal variation in the NAc (Falcon et al, 2013), as well as rhythmicity measured by Per2 :luciferase luminescence assays (Logan et al, 2015). This is further supported by studies from the Welsh group demonstrating NAc Per2 :luciferase rhythms (Landgraf, Long, & Welsh, 2016; Porcu et al, 2020), as well as diurnal variation in CRYPTOCHROME protein levels in the NAc (Porcu et al, 2020). Interestingly, this is also seen in time of death analyses of gene expression in human post‐mortem tissue, where the canonical clock genes (e.g., Bmal1 , Npas2 , Period , Cryptochrome , Rev‐erbα ) are all highly rhythmic in the NAc of healthy donors (Ketchesin et al, 2021; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 74%
“…The knockdown Bmal1 expression restricted to the SCN could increase depressive-and anxiety-like behaviors in mice (Landgraf et al, 2016). CRY in nucleus accumbens was found to regulate depressive-like behaviors in mice (Porcu et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Studies in both rodents and human post-mortem tissue have shown significant rhythmicity in NAc circadian molecular clock function. Using the PER2:LUC mouse model, sustained bioluminescent rhythms have been detected in the NAc ex vivo ( Logan et al, 2015 ; Landgraf et al, 2016a ; Porcu et al, 2020 ). This corroborates gene expression analyses in mice showing significant diurnal variation in molecular clock mRNA levels in the NAc ( Falcon et al, 2013 ; Natsubori et al, 2014 ; Logan et al, 2015 ; Brami-Cherrier et al, 2020 ; Porcu et al, 2020 ; Becker-Krail et al, 2022b ), as well as protein expression analyses in the striatum ( Schnell et al, 2015 ).…”
Section: The Nucleus Accumbens As a Circadian Oscillatormentioning
confidence: 99%
“…Using the PER2:LUC mouse model, sustained bioluminescent rhythms have been detected in the NAc ex vivo ( Logan et al, 2015 ; Landgraf et al, 2016a ; Porcu et al, 2020 ). This corroborates gene expression analyses in mice showing significant diurnal variation in molecular clock mRNA levels in the NAc ( Falcon et al, 2013 ; Natsubori et al, 2014 ; Logan et al, 2015 ; Brami-Cherrier et al, 2020 ; Porcu et al, 2020 ; Becker-Krail et al, 2022b ), as well as protein expression analyses in the striatum ( Schnell et al, 2015 ). This is also seen in human post-mortem NAc tissue RNA-sequencing analyses where transcript levels are organized by time-of-death and tested for rhythmicity.…”
Section: The Nucleus Accumbens As a Circadian Oscillatormentioning
confidence: 99%